Pro-environmental behavior and environmentalist movements: Evidence from the identification with Fridays for Future - Daniela Flörchinger; Manuel Frondel; Stephan Sommer; Mark Andreas Andor (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Using identification with the environmentalist movement Fridays for Future, this paper empirically tests the effect of a novel type of prime on pro-environmental behavior: the reminder of their previously stated attitude towards Fridays for Future. On the basis of a large-scale survey experiment including the incentivized choice between a voucher for a flight or a train ride, we find evidence that respondents who receive such an identity prime are more likely to behave in line with the movement's moral principles in that they take the train. Our results suggest that pro-environmental behavior may be enhanced by reminding individuals of their attitude towards environmental matters. – – Anhand der Identifikation mit der Umweltbewegung Fridays for Future wird in diesem Beitrag empirisch die Wirkung einer neuen Art von Prime auf umweltfreundliches Verhalten getestet: die Erinnerung an die zuvor geäußerte Einstellung zu Fridays for Future. Auf der Grundlage eines groß angelegten Umfrageexperiments, das die Wahl zwischen einem Gutschein für einen Flug oder eine Zugfahrt vorsieht, finden wir Hinweise darauf, dass die Befragten, die einen solchen Prime erhalten haben, sich mit größerer Wahrscheinlichkeit im Einklang mit den moralischen Prinzipien der Bewegung verhalten, indem sie den Zug wählen. Unsere Ergebnisse deuten darauf hin, dass umweltfreundliches Verhalten durch die Erinnerung an die eigene Einstellung zu Umweltfragen gefördert werden kann.
Keywords: D81; D91; 330; Pro-social behavior; priming; cognitive dissonance